2020
DOI: 10.3329/bmrcb.v46i2.49015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitudes and practices towards prevention of coronavirus disease (COVID-19) among Bangladeshi population

Abstract: Background: Cornonavirus disease (COVID-19) has been declared pandemic by the World Health Organization on the 11th March 2020. The knowledge, attitudes and practices of the population towards the COVID-19, play an integral role in determining community’s readiness to engage themselves in government measures including behavioural change in prevention and control of the disease. Objectives: The study was aimed to determine the knowledge levels, attitudes and practices towards the COVID-19 among the Bangla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 8 publications
4
10
0
Order By: Relevance
“…According to our study, participants with a higher level of education were found to have more knowledge about COVID-19 vaccinations, which is also supported by previous research. Similar scenarios were found in other earlier studies in Bangladesh, illustrating that individuals with a higher educational background showed more knowledge regarding COVID-19 [ 27 , 31 ]. It may be the case that more educated people are more knowledgeable and concerned about their health and well-being, through access to more information sources, and become more engaged in life events that could impact them [ 32 ], such as COVID-19 vaccinations.…”
Section: Discussionsupporting
confidence: 89%
“…According to our study, participants with a higher level of education were found to have more knowledge about COVID-19 vaccinations, which is also supported by previous research. Similar scenarios were found in other earlier studies in Bangladesh, illustrating that individuals with a higher educational background showed more knowledge regarding COVID-19 [ 27 , 31 ]. It may be the case that more educated people are more knowledgeable and concerned about their health and well-being, through access to more information sources, and become more engaged in life events that could impact them [ 32 ], such as COVID-19 vaccinations.…”
Section: Discussionsupporting
confidence: 89%
“…According to our study, participants with a higher level of education were found to have more knowledge about COVID-19 vaccinations, which is also supported by previous research. Similar scenarios were found in other earlier studies in Bangladesh, illustrating that individuals with a higher educational background showed more knowledge regarding COVID-19 [25,29]. It may be the case that more educated people are more knowledgeable and concerned about their health and well-being, through access to more information sources, and become more engaged in life events that could impact them [30], such as COVID-19 vaccinations.…”
Section: Discussionsupporting
confidence: 81%
“…The highly infectious novel corona virus disease that was first identified Wuhan, China, the causative agent was initially named as 2019 novel corona virus (2019-nCOV) which later was renamed as SARS-CoV-2 and the disease it caused was named as corona virus disease 2019(2019-nCOV). 1,2,3 On the 30 th January, 2020, the World Health Organization (WHO) declared that the outbreak constitutes a Public Health Emergency of International Concern (PHEIC) and as global pandemic on the 11 th March 2020 3,4 The COVID-19 pandemic is associated with increasing morbidity and mortality and has impacted the lives of the global population. 3,5 SARS-CoV-2 is an enveloped non-segmented RNA virus.…”
Section: Introductionmentioning
confidence: 99%